2010
DOI: 10.1007/s10822-010-9336-6
|View full text |Cite
|
Sign up to set email alerts
|

Using a homology model of cytochrome P450 2D6 to predict substrate site of metabolism

Abstract: CYP2D6 is an important enzyme that is involved in first pass metabolism and is responsible for metabolizing ~25% of currently marketed drugs. A homology model of CYP2D6 was built using X-ray structures of ligand-bound CYP2C5 complexes as templates. This homology model was used in docking studies to rationalize and predict the site of metabolism of known CYP2D6 substrates. While the homology model was generally found to be in good agreement with the recently solved apo (ligand-free) X-ray structure of CYP2D6, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 68 publications
1
29
0
1
Order By: Relevance
“…Predictions were deemed correct in cases where a known SOM is located within a 4.5 Å distance from the catalytic center among the five highestranked poses. This was found to be correct for 85% of the 16 investigated compounds [316]. This study points out the common observation that, due to considerable conformational rearrangements of the protein upon ligand binding, P450 apo structures generally yield inferior performance compared to holo structures.…”
Section: Metabolite Predictionsupporting
confidence: 64%
“…Predictions were deemed correct in cases where a known SOM is located within a 4.5 Å distance from the catalytic center among the five highestranked poses. This was found to be correct for 85% of the 16 investigated compounds [316]. This study points out the common observation that, due to considerable conformational rearrangements of the protein upon ligand binding, P450 apo structures generally yield inferior performance compared to holo structures.…”
Section: Metabolite Predictionsupporting
confidence: 64%
“…8A-E). It has been reported that Phe120, Glu216, Asp301, Phe481 and Phe483 are key amino acid residues for substrate interaction within in the active site of CYP2D6 (McLaughlin et al, 2005;Unwalla et al, 2010). Alanine substitution of Phe120 had only a minor effect on the inhibition and binding activity, whereas alanine substitution of Glu216 and Asp301 played a significant role in binding to CYP2D6 active site in productive orientation.…”
Section: Molecular Docking Studiesmentioning
confidence: 99%
“…For more than 75% of the substrate, the X-ray structure fails to rationalize the metabolism in terms of the binding modes [45]. Similar results were observed in a comparison of another homology model with the X-ray structure [46]. One of the substrates that were successfully docked into the X-ray structure was 3,4-methylenedioxy-N-ethylamphetamine.…”
Section: Protein Flexibilitymentioning
confidence: 55%